Transient Photocurrent Elucidating Carrier Dynamics and Potential of Bulk Heterojunction Solar Cells Fabricated by Thermal Precursor Approach. Issue 5 (6th March 2018) - Kudo, Naoki; Uchida, Ken; Ikoma, Tadaaki; Takahashi, Kohtaro; Kuzuhara, Daiki; Suzuki, Mitsuharu; Yamada, Hiroko; Kumagai, Daichi; Yamaguchi, Yuji; Nakayama, Ken‐Ichi
Abstract : Transient photocurrents are measured to clarify carrier dynamics in a series of bulk heterojunction solar cells that are composed of [6, 6]‐phenyl‐C61 ‐butyric acid methyl ester (PCBM) and diketopyrrolopyrrole‐tetrabenzoporphyrin conjugates substituted by straight alkyl groups (Cn‐DPP‐BP), of which the device parameters are largely dependent on the length of the substituted alkyl groups (Cn). The time profile of the observed transients indicates the presence of both unimolecular and bimolecular charge recombination processes in the active layer of the cells. Analysis of the photocurrent decays detected at various bias voltages using a drift model that considers charge extraction by electrodes and charge recombination in the active layer enables elucidation of the charge drift mobility, the initial photocarrier density, and the charge recombination rate constants. The bimolecular recombination rate constant is correlated with Cn and this is the main factor that determines the power conversion efficiency ( η ) of the Cn‐DPP‐BP:PCBM solar cells. The Cn‐dependent fill factor can be interpreted in terms of the bias voltage dependence of the ratio between the extraction and recombination charges ( Q ex / Q re ). Comparison of η and Q ex / Q re at the short‐circuit condition predicts that η for the Cn‐DPP‐BP:PCBM solar cell can be potentially improved up to 6%. Abstract : Transient photocurrents in bulk heterojunction organic solar cells comprised of small molecules indicate that nongeminate recombination is the main reason for degradation of the power conversion efficiency ( η ) and is strongly dependent on the length of the alkyl chain substituted on the p‐type compound. Comparison between the kinetic constants and the device parameters provides a potential η, which is useful to improve the cell and achieve high‐efficiency.